Glucose is an active chemical agent on degradation of hydroxyapatite nanostructure - Martins, Murillo L.; Iessi, Isabela L.; Quintino, Michelle P.; Damasceno, Débora C. [UNESP]; Rodrigues, Cloves G. (Elsevier, 2020)
The mechanisms governing the glucose/bone mineral interface are still not fully described. By recognizing the multidisciplinary character of this problem, in this work we exclude any biological variable and provide insight with a pure materials science perspective. For that, hydroxyapatite nanoparticles were prepared in media with glucose concentrations analogous to those found in healthy and diabetic patients. We report that the influence of glucose over the nanoparticles depends on the stage in which it is added to the synthesis. First, nanoparticles precipitated in glucose-rich solutions present, as expected, decrease in crystallinity. However, this effect is driven by the action of glucose as an active chemical agent, rather than simply as a dispersant. This effect becomes more severe when hydroxyapatite nanoparticles are separately prepared and further allowed to interact with glucose. In this scenario, the deterioration of the nanoparticles’ bulk structure accompanies increase in surface crystallinity. In general, the effects of glucose over hydroxyapatite are concentration-dependent and associated with the precipitation of secondary phases - calcium hydroxide and calcium carbonate. Finally, we present illustrative data from bone minerals from one diabetic and one healthy rat and show that our methods and outcomes are employable in future biomedical investigations.
Keywords: Glucose; Hydroxyapatite; Infrared spectroscopy; X-ray diffraction